Evaluation of Imaging Methods in Tick-Borne Encephalitis - Zawadzki, Radosław (Pol J Radiol, 2017)
Tick-borne encephalitis (TBE) is caused by a virus that belongs to the Flaviviridae family and is transmitted by tick bites. The disease has a biphasic course. Diagnosis is based on laboratory examinations because of non-specific clinical features, which usually entails the detection of specific IgM antibodies in either blood or cerebrospinal fluid that appear in the second phase of the disease. Neurological symptoms, time course of the disease, and imaging findings are multifaceted. During the second phase of the disease, after the onset of neurological symptoms, magnetic resonance imaging (MRI) abnormalities are observed in a limited number of cases. However, imaging features may aid in predicting the prognosis of the disease.